Legal Certainty of Management Rights of Lejja Nature Tourism Park, Soppeng Regency Perspective of Siyasah Tasyri'iyyah - Sri wahyuni; Rusdianto Sudirman (JURNAL SULTAN: Riset Hukum Tata Negara, 2025)
This study discusses legal certainty in the management of the Lejja Nature Tourism Park (TWA) of Soppeng Regency from the perspective of Siyasah Tasyri'iyyah. The main focus of this research is the analysis of the division of authority between the Natural Resources Conservation Center (BBKSDA) and PT. Mataesso Mattappa in the management of the tourist area. The purpose of this study is to examine the legal certainty of the management rights of TWA Lejja and evaluate its management based on the principles of Siyasah Tasyri'iyyah. This study uses a qualitative method with a sociological juridical approach. Data was collected through observations, interviews with BBKSDA, PT. Mataesso Mattappa, and tourists, as well as the study of documents related to applicable legal regulations. The theories used in the analysis include the theory of legal certainty, the division of power, and Siyasah Tasyri'iyyah. The results of the study show that the management of TWA Lejja has not fully reflected legal certainty due to the overlap of authority between BBKSDA as a regulator and PT. Mataesso Mattappa as operational manager. Despite the division of duties, its implementation is still not optimal in applying the principles of Siyasah Tasyri'iyyah, especially in the aspects of justice and trust for environmental conservation and community empowerment.